2017
DOI: 10.1111/apa.13711
|View full text |Cite
|
Sign up to set email alerts
|

Area‐based study shows most parents follow advice to reduce risk of sudden infant death syndrome

Abstract: AimGuidance on reducing the risk of sudden infant death syndrome (SIDS) was successfully introduced to a number of countries in the early 1990s. The most important recommendations were supine sleeping for infants and non‐smoking for mothers. This 2012–2014 study examined adherence to the national Swedish SIDS advice.MethodsWe asked 1000 parents with infants registered at child healthcare centres in western Sweden to complete a questionnaire on infant care from birth to 12 months of age.ResultsWe analysed 710 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
5
12
0
1
Order By: Relevance
“…It is unclear if every case of SUID was included. Total live births in Sweden 2002–2011 numbered 762,626 came from Statistika centralbyrån‐ Statistics Sweden (). Smoking in pregnancy data came from Zeitlin et al (). Swedish 2010–2014 bedsharing and sleep position data came from Stromberg Celind et al ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear if every case of SUID was included. Total live births in Sweden 2002–2011 numbered 762,626 came from Statistika centralbyrån‐ Statistics Sweden (). Smoking in pregnancy data came from Zeitlin et al (). Swedish 2010–2014 bedsharing and sleep position data came from Stromberg Celind et al ().…”
Section: Resultsmentioning
confidence: 99%
“…Among Japanese, Swedes, and Asian Americans, both breastfeeding and bedsharing are very common (Table ). Sweden had the highest bedsharing rate in all of Western Europe (Nelson et al, ), although it has decreased with recommendations against bedsharing (Stromberg Celind, Wennergren, Möllborg, Goksor, & Alm, ). With universal implementation of the Baby‐Friendly Hospital Initiative, Sweden also has exceptionally high breastfeeding rates (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study done in Sweden, only 50.9% of infants below three months slept in their own cribs [ 11 ]. The percentage rose to 57.9% in those who were three to six months old, while another study in the United States showed a similar percentage of 48.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Expectant mothers also receive advice on a healthy lifestyle during pregnancy, on breast feeding and on safe sleeping positions for their new baby 6. There is a strong historical tradition in Sweden that people trust and listen to the authorities.…”
mentioning
confidence: 99%